Historical analysis of the evolution of Brazilian Education (Research, Society and Development, 2023)
Reflecting and understanding the history of Education is extremely important so that we can understand the current educational situation and what happened in this historical process. In this sense, the article brings a reflection on the theme “history of Brazilian Education”, aiming at a historical analysis of Brazilian Education from its beginnings to the present day. The methodological procedure used was the bibliographical one, with a qualitative approach. Data collection took place through the search platforms “Periódico Capes” and “Google Acadêmico”, using the following descriptors: History of Education”, “Evolution of Education”, “Historical Analysis of Education”, without a time frame , with the works selected according to the interests of the researchers. For the analysis of the results, the Free Interpretation Analysis (ALI) was chosen. The results of the study indicate that since the most remote times there has been a need for human training, communication and writing. Analyzing this Education since the Jesuit Period; and passing through the Johannine Period; Imperial period; First Republic; Second Republic; New state; New Republic; Military Regime to the present day it can be concluded that a lot has changed, but there is still a lot to change. Laws, decrees, schools, universities, policies were created, Education that was only provided for a minority of the population (nobles) became the right of all, which in fact was a great advance for society.